The Anscombean mind - Haddock, Adrian; Wiseman, Rachael ca. 20./21. Jh (Routledge, 2022)
"G. E. M. Anscombe (1919-2001) is one of the most important philosophers of the twentieth century. Known primarily for influencing research in action theory and moral philosophy, her work also has relevance in the study of metaphysics, philosophy of language, philosophy of mind, philosophy of religion, and politics. The Anscombian Mind provides a comprehensive survey of Anscombe's thought, not only placing it in its historical context but also exploring its enduring significance in contemporary debates. Divided into three clear parts, 24 chapters by an international team of contributors address the following themes: ancient philosophy metaphysics mind and language Wittgenstein action and ethics politics religion and faith. Also included is Anscombe's 1948 Mary Somerville Fellowship Report, making this fascinating document easily available to readers for the first time. The Anscombian Mind is an indispensable resource for anyone studying and researching Anscombe herself, action theory, ethics, moral philosophy, Wittgenstein, and twentieth-century philosophy"--
Keywords: Anscombe, G. E. M. -- 1919-2001; Philosophie; Anscombe, G. E. M. / (Gertrude Elizabeth Margaret); Aufsatzsammlung